Konceptuelle metaforer som selektionskriterium for Dansk litteraturs kanon - med fokus på elevers literacytilegnelse på tværs af tidsrum, sprog og kultur i arbejdet med kanonlitteratur - Kaasby, Mia (Nordlit, 2022)
This article argues that an increased focus on the inherent conceptual metaphors of chronotopes in canonical literature may contribute to students’ awareness of the historical and literary development in time and space. Thus, expanding their literacy-skills acquisition in comparison to the linear chronological periodization, author-portrait and text reading that typically characterize the reading of canon literature. Furthermore, the article argues that an increased focus on bi- and multilingual students’ interpretation of conceptual metaphors may contribute to the historical and literary development.
Keywords: conceptual metaphors; chronotop; literacy; canonical literature